The influence of high myopia-related exotropia on surgical dose–response in unilateral recession and resection surgery: a retrospective study - Chao Li; ZhiYin Lou; Fan Yang (Frontiers in Medicine, 2025)
ObjectiveTo investigate the impact of high myopia on the surgical dose–response in unilateral recession and resection (R&R) surgery for exotropia.MethodsA retrospective analysis was conducted on 101 Chinese patients who underwent unilateral R&R surgery for concomitant exotropia between June 2021 and June 2024. Patients were divided into two groups based on axial length: those with high myopia (n = 38) and those without high myopia (n = 63). Surgical doses for lateral rectus (LR) recession and medial rectus (MR) resection were compared between the groups. Preoperative and postoperative deviations were measured, and statistical analyses were performed to assess the relationship between surgical dose, axial length (AL), and other clinical variables.ResultsAge, duration of exotropia, and AL differed significantly between the groups, but other baseline characteristics were comparable. The LR recession dose did not differ significantly between the high myopia group (6.40 ± 1.11 mm) and the non-high myopia group (6.74 ± 1.00 mm, p > 0.05). However, the MR resection dose was significantly lower in the high myopia group (5.77 ± 1.02 mm) compared to the non-high myopia group (6.32 ± 0.92 mm, p < 0.05). The MR resection and LR recession dose was positively correlated with the horizontal deviation (p < 0.001), but showed no significant correlation with AL (p > 0.05).ConclusionExotropia with high myopia had a greater surgical dose response than those without high myopia. No significant difference was found in LR recession dose, but the MR resection dose was significantly lower in the high myopia group.